2017
DOI: 10.4094/chnr.2017.23.4.479
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Home-Based Intervention Program to Prevent Child Abuse for Parents: A Meta Analysis

Abstract: Background: Consistent findings about the effectiveness of parent programs to prevent or reduce child maltreatment are lacking.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 49 publications
0
3
0
1
Order By: Relevance
“…In the case of existing systematic reviews and meta-analyses, researchers reviewed the prevalence of the main forms of CM, and their relationships with depression, as well as other mental and behavioral problems, such as anxiety and suicidality, that took place in childhood, young adulthood, or middle adulthood, while some other studies were conducted among samples of mixed ages (Angelakis et al, 2019; Azzopardi et al, 2019; Gardner et al, 2019; Nelson et al, 2017; Norman et al, 2012; Paolucci et al, 2001; Vlahovicova et al, 2017). Some studies have further reviewed the effect of programs aimed at preventing specific effects of CM (Ji & Finkelhor, 2015; Park & Kim, 2017; Van de Put et al, 2018; Walsh et al, 2018). Two major limitations of previous research are identified: First, LLD was not set as a particular research variable, despite its high prevalence and burdensome consequences; Second, previous research has not yet determined and compared the effect sizes of the major aspects of CM on LLD.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of existing systematic reviews and meta-analyses, researchers reviewed the prevalence of the main forms of CM, and their relationships with depression, as well as other mental and behavioral problems, such as anxiety and suicidality, that took place in childhood, young adulthood, or middle adulthood, while some other studies were conducted among samples of mixed ages (Angelakis et al, 2019; Azzopardi et al, 2019; Gardner et al, 2019; Nelson et al, 2017; Norman et al, 2012; Paolucci et al, 2001; Vlahovicova et al, 2017). Some studies have further reviewed the effect of programs aimed at preventing specific effects of CM (Ji & Finkelhor, 2015; Park & Kim, 2017; Van de Put et al, 2018; Walsh et al, 2018). Two major limitations of previous research are identified: First, LLD was not set as a particular research variable, despite its high prevalence and burdensome consequences; Second, previous research has not yet determined and compared the effect sizes of the major aspects of CM on LLD.…”
Section: Introductionmentioning
confidence: 99%
“…Hundreds of trials have examined the effects of preventive mental health interventions in school-aged youth (Tanner-Smith, Durlak, & Marx, 2018;Skeen et al, 2019), university students (Cole, Prassel, & Carlson, 2018;Conley, Durlak, & Kirsch, 2015;Conley, Shapiro, Kirsch, & Durlak, 2017), and at the workplace (Bartlett et al, 2019;Carolan, Harris, & Cavanagh, 2017;Tan et al, 2014). Hundreds more trials have examined the effects of preventive interventions aimed at high risk groups for developing mental health problems, including caregivers of patients with dementia (Cheng et al, 2020;Walter & Pinquart, 2019), children of parents with mental disorders (Siegenthaler, Munder, & Egger, 2012), people who suffer from a recent trauma (Roberts, Kitchiner, Kenardy, Lewis, & Bisson, 2019), patients with cancer (Zahid, Grummedal, Tvilling Madsen, & Gögenur, 2020), and programs aimed at prevention of postpartum depression (Sockol, Epperson, & Barber, 2013) and child abuse (Park & Kim, 2017;Walsh, Zwi, Woolfenden, & Shlonsky, 2018).…”
Section: Editorialmentioning
confidence: 99%
“…Selective interventions aimed at high-risk groups include, for example, programs aimed at preventing child abuse (Park and Kim, 2017 ; Walsh et al, 2018 ) and support programs for caregivers of frail elderly (Cheng et al, 2020 ) or caregivers of relatives of patients with mental disorders (Chien et al, 2018 ). Most of these interventions do not focus directly on preventing the onset of depressive disorders, although there are exceptions like programs that aim at preventing depression in children of parents with depression (Siegenthaler et al, 2012 ).…”
Section: Introductionmentioning
confidence: 99%